Where Can Agricultural Research Most Contribute to Winning More and Losing Less? Key Insights and Implications for CGIAR from Science Forum 2018 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2018)
This brief summarizes discussions at Science Forum 2018 (SF18), organized around four main building blocks (1. Research design; 2. Prioritizing activities; 3. Measuring success; and, 4. Demonstrating impact) that the Forum participants were asked to consider in every session.